Predictive Value of Angiographic Testing for Tolerance to Therapeutic Occlusion of the Carotid Artery - van Rooij, Willem Jan (AJNR Am J Neuroradiol, 2005)
BACKGROUND AND PURPOSE: Controversy exists on how to assess a patient’s tolerance before permanent carotid artery occlusion. We sought to determine the positive predictive value of synchronous opacification of hemispheric cortical veins at angiography of the contralateral carotid or vertebral artery as a predictor of tolerance to permanent carotid artery occlusion without development of ischemic injury. METHODS: Seventy-six angiographic test occlusions were performed in 74 consecutive patients considered for therapeutic occlusion. Angiography of collateral cerebral vessels was performed during test occlusion. Synchronous filling (a < 0.5-second delay of opacification between the cortical veins of the occluded and collateral vascular territories) was considered a predictor for tolerance to permanent occlusion. To detect clinically silent ischemic defects, MR imaging was performed before and 6–12 weeks after permanent occlusion. Positive predictive value (95% confidence interval [CI]) of synchronous venous filling for absence of ischemic deficits after permanent occlusion was calculated. RESULTS: No procedural complications of the test occlusion occurred. In 51 of 54 patients who passed the test, permanent occlusion was performed. Two patients, both in poor clinical condition after subarachnoid hemorrhage, died of diffuse vasospasm after permanent occlusion. Of the 49 surviving patients, one developed a transient discrete hemiparesis with small new hypoperfusion infarctions on MR images. All other patients remained neurologically unchanged with no new ischemic lesions on follow-up MR images. Positive predictive value of tolerance to carotid artery occlusion after passing the angiographic test was 98% (95% CI: 89–100%). CONCLUSION: The angiographic test occlusion protocol reliably predicts tolerance to therapeutic carotid artery occlusion. It is safe and easy to perform.